Effect of varying 9-Octadecenoic acid (oleic fatty acid) content in biofuel on the performance and emission of a compression ignition engine at varying compression ratio. Issue 4 (4th July 2018) - Dinesha, P.; Jagannath, K.; Mohanan, P.
ABSTRACT: The 9-Octadecenoic acid (oleic fatty acid) content of vegetable oil seeds can be altered by mutagenesis, thereby increasing its content in the oil, for the purpose of increasing shelf life. In this work, the effect of varying the oleic acid content in ester on the performance and emission of a CI engine was examined. For this purpose, the situation was simulated by adding commercially available 9-Octadecenoic acid to pongamia ester; in terms of different percentages, the experiments were conducted with 10% and 20% extra oleic acid, at 16, 17, 17.5 and 18 compression ratio (CR). The results indicate that the smoke emission and BSEC increase with increase in oleic acid content, whereas the BTE and NOx decrease with increased proportions of oleic acid for all CRs. Pongamia methyl ester with 10% extra oleic acid at 17 CR results in lower NOx when compared to neat pongamia methyl ester at a normal CR of 17.5. Smoke emission increases with extra oleic acid content for all CRs; however, it is minimum at 17 CR for 10% extra oleic acid. From the research it is concluded that pongamia methyl ester with 10% extra oleic acid at 17 CR results in better performance and emission.